Circle Fish and the Women of Perlis Village (Ethnography Study of the Women in Perlis Village, Brandan Barat, Langkat Regency) - Masliawati, Suci; Pujiraharjo, Sidarta (Universitas Muhammadiyah Malang, 2023)
Cerbung fish is one of the fish caught by fishermen in Perlis Village. Dried cerbung fish is a superior product in the fisheries sector which is in demand by the wider community besides that it is also the catch that is most in demand as a life support for the fishing community of Perlis Village. In the process of processing dried cerbung fish it does not only involve fishermen, but Perlis women also have quite an important role, namely as splitters of cerbung fish. North Sumatra. This method uses a qualitative method with an ethnographic study approach that is carried out as a live-in (living together) community by making observations (participatory observation as well as conducting interviews with informants. The results of the study show that female cerbung fish splitters have an important role in the fishermen's household economy. When the turtledove season arrives, from March to November, the income of women who work as swordfish splitters increases compared to their other jobs.However, these women receive less special attention from the community.